User Satisfaction of Environmental Quality in University Buildings - Erbil, Yasemin; Sezer, F. Senkal (European Journal of Sustainable Development, 2016)
In this study, user satisfaction with environmental quality in university buildings are investigated. The buildings that were selected for the study are the School Medicine, Veterinary School and Faculty of Agriculture buildings located at Uludag University Görükle Campus, Bursa, Turkey. A user satisfaction questionnaire developed by the authors was used to evaluate the level of satisfaction of the users in these buildings. The key themes selected were design - planning, physical environmental control, and social environment parameters. Design - planning parameter is evaluated by accessibility and reachability criteria; physical environmental control parameter is evaluated by thermal comfort, audial comfort and visual comfort criteria; and social environment parameter is evaluated by service areas and socializing criteria. The survey form, which is based on a Likert type was applied to 100 users in each building, reaching a total of 300 users. The data collected was analyzed by percentages. According to the research results, the proximity of buildings to the center of the campus, ability to easily access different storeys in buildings, ensuring thermal comfort conditions are created, not using artificial air conditioning, blocking noise from external and internal sources, fulfilling visual comfort conditions, adequate number of wet areas and car parks, establishment of eating, drinking and resting spaces, spaces for social interaction and adequate landscaping and green areas and the ability to effectively use open spaces are among the factors that influence user satisfaction in buildings. Keywords: environmental quality, user satisfaction questionnaire, university buildings